Godsend - Butan, Marc.; Schulman, Cathy; O'Keefe, Sean.; Bomback, Mark.; Hamm, Nick, 1957-; Kinnear, Greg, 1963-; Romijn, Rebecca, 1972-; De Niro, Robert; Bright, Cameron, 1993-; Morgenthau, Kramer; Mirkovich, Steve; Howie, Niven; et al. (Santa Monica, Calif. : Lions Gate Home Entertainment, 2004)
Paul and Jessie are devastated when their 8-year-old son dies. When a fertility expert offers them an opportunity to resurrect their boy through a secret and illegal cloning procedure, they don't know that the doctor's hidden agenda will have horrifying repercussions when their "new" son passes his eighth birthday. Adam begins having "night terrors" and begins having marked changes in his behavior, and he begins to display a palpable sense of menace. Paul and Jessie cannot escape the fact that this Adam is different.
Director of photography, Kramer Morgenthau ; editors, Steve Mirkovich, Niven Howie ; music composer, Brian Tyler ; costume designer, Suzanne McCabe ; production designer, Doug Kraner.
Greg Kinnear, Rebecca Romijn-Stamos, Robert De Niro, Cameron Bright.
MPAA rating: PG-13; for violence including frightening images, a scene of sexuality and some thematic material.
DVD, Region 1, widescreen presentation; Dolby Digital, DTS.
Closed-captioned.
Keywords: Human cloning -- Drama; Fertility clinics -- Drama; Physician and patient -- Drama; Fertility clinics; Human cloning; Physician and patient; Drama; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired; Feature films; Films for the hearing impaired; DVD-Video discs; Thrillers (Motion pictures); Feature films; Video recordings for the hearing impaired; Suspense films